Double Movement : Aktualisasi Pemikiran Fazlur Rahman dalam Hukum Islam - Zumaroh Zumaroh; Siti Nurjanah; Agus Hermanto; Siti Zulaikha (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This article discusses the Double Movement theory developed by Fazlur Rahman as a hermeneutic method in the renewal of Islamic law. This theory emphasizes two main movements: first, understanding the socio-historical context of the revelation of the Qur'an to explore universal moral values ​​behind legal provisions; second, actualizing these values ​​into contemporary social and cultural contexts. Through a literature review and case analysis on aspects of family law and economic law in Indonesia, this article shows how the Double Movement theory provides more flexible, dynamic, and relevant interpretive solutions. This approach allows Islamic law to adapt to modern social dynamics without losing its transcendental moral essence. In addition, this approach opens up space for progressive and contextual ijtihad, which is greatly needed in responding to various new challenges in Muslim society. Thus, this theory makes an important contribution to the development of an Islamic legal methodology that is responsive and inclusive to the changing times.